Oxidative stress is involved in heat-induced cell death in Saccharomyces cerevisiae. - Davidson, J F (1996)
The cause for death after lethal heat shock is not well understood. A shift from low to intermediate temperature causes the induction of heat-shock proteins in most organisms. However, except for HSP104, a convincing involvement of heat-shock proteins in the development of stress resistance has not been established in Saccharomyces cerevisiae. This paper shows that oxidative stress and antioxidant enzymes play a major role in heat-induced cell death in yeast. Mutants deleted for the antioxidant genes catalase, superoxide dismutase, and cytochrome c peroxidase were more sensitive to the lethal effect of heat than isogenic wild-type cells. Overexpression of catalase and superoxide dismutase genes caused an increase in thermotolerance. Anaerobic conditions caused a 500- to 20,000-fold increase in thermotolerance. The thermotolerance of cells in anaerobic conditions was immediately abolished upon oxygen exposure. HSP104 is not responsible for the increased resistance of anaerobically grown cells. The thermotolerance of anaerobically grown cells is not due to expression of heat-shock proteins. By using an oxidation-dependent fluorescent molecular probe a 2- to 3-fold increase in fluorescence was found upon heating. Thus, we conclude that oxidative stress is involved in heat-induced cell death.